English - chinese translation app for Android A - Yew, Su Ying (2015)
Despite Singapore being a Little Red Dot on the world map, it has attracted many tourists around the world. This is a contributing factor for rapid growth in tourism in the recent years. With the growth of tourism, it will help to advance Singapore’s economy. However, it will lead to another problem between the tourists and the shopkeepers/retailers, which is the language barrier. Most of the shopkeepers in Singapore may not know multiple languages. Therefore, it is very difficult for them to communicate or sell their products to the tourists and may cause the shopkeepers to lose their customers. To solve this problem, the sellers or tourists can download this translator application to help in translating from one language to another language. This translator allows users to input the text in three different methods: soft keypad, Google speech reorganization and camera capture (Optical Character Recognition). After entering the text that the user wishes to translate, the application will automatically translate the text via Bing translator service. The application also makes use of the text to speech function in android to give user a better usability. Furthermore, the translated words can be shared with others via application such as WhatsApp, Email, SMS and more. A History List is also provided in this application for the user to check for past translated text. Hence, if the user wants to recall the words that he or she had translated before, or wants to translate into another language, they can tap on the word. In addition, the users can also translate their SMS messages to their desire language through our application. A dictionary function is also implemented for user to check the definition of the word that they are translating.